2015
DOI: 10.3188/szf.2015.0168
|View full text |Cite
|
Sign up to set email alerts
|

Die Schutzfunktion in Windwurfflächen

Abstract: Protection against natural hazards on windthrow areas We give an overview on natural hazard processes on windthrow areas during the first 20 years after the winterstorm Vivian (1990). This overview is based on 1) repeated pulling experiments and a long-term analysis of stem movements in the uncleared winthrow area Cavorgia/Disentis, 2) the assessment of avalanche protection function of 26 windthrow areas, and on (3) StorMe cadastral data of natural hazard events on windthrow areas. The effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…Other positive feedbacks can result from the removal of biomass due to windthrow, fire, or other disturbance and subsequent gravitational hazards like avalanches, rockfall, or shallow landslides. Such interactions are of particular societal importance in the densely populated Alps, and more knowledge is needed on interactions between a broad range of disturbance agents, in different forest types, and under different management regimes (Conedera et al, 2003; Bebi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Other positive feedbacks can result from the removal of biomass due to windthrow, fire, or other disturbance and subsequent gravitational hazards like avalanches, rockfall, or shallow landslides. Such interactions are of particular societal importance in the densely populated Alps, and more knowledge is needed on interactions between a broad range of disturbance agents, in different forest types, and under different management regimes (Conedera et al, 2003; Bebi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of old disturbed forest, a roughness time-series analysis might not distinguish between the roughness of old fallen logs, lower vegetation and tree regeneration. After years of decomposition, the fallen logs become less supportive, decrease in height, are moved and even decompose completely (Bebi et al, 2015;. A comprehensive overview of the decay process over a longer period after a disturbance (more than 20 years) would be helpful to understand the function of time and the remaining protection capacity after a disturbance such as windthrow.…”
Section: Applications For Natural Hazard Assessmentmentioning
confidence: 99%
“…However, some tensile tests showed a reduction of the breaking point of logs, mainly due to the decay of wood. It was also observed that the level of decay was related to the microsite, mainly the height above ground of logs and their vegetation cover [39]; the presence of bark on logs may also influence the speed of decaying processes [40]. Although we were able to observe and quantify the protective role played by structural legacies, it is important to underline that this role is strictly connected with the type of disturbance that hit the protection forest.…”
Section: Discussionmentioning
confidence: 88%
“…The facilitation effect provided by deadwood can be fundamental for speeding up natural regeneration processes. The presence of biological legacies, indeed, may not only provide protection, but also create the condition for shortening the protection gap, which should be the main target of management strategies for a damaged protection forest [1,12,39].…”
Section: Discussionmentioning
confidence: 99%